Improving Visual Communication of Science Through the Incorporation of Graphic Design Theories and Practices Into Science Communication. (February 2015) - Rodríguez Estrada, Fabiola Cristina; Davis, Lloyd Spencer
Visual culture is becoming an increasingly prominent part of our cultural identity in the 21st century. Consequently, images have become an important tool with which to communicate science. We identify two impediments to science communicators using visual elements effectively: (1) visual material is typically treated as an add-on instead of being an integrated part of the whole and (2) there is a lack of identifying target audiences and refining visual elements for them specifically. We argue that science communicators can become more effective visual communicators if they incorporate elements of theory and practice from the discipline of design.